Transforming University Learner Support in Open and Distance Education: Staff and Students Perceived Challenges and Prospects - Ouma, Richard (Cogent Education, 2019)
This article cross-examines the views of the university staff and selected students on institutional challenges in managing and delivering learner support for in-service teachers engaged in distance education in Uganda. A qualitative approach using in-depth interviews and reflective logs provided the study framework. The results showed several challenges faced by the university in administering learner support: a limited number of full-time staff at the faculty, lack of a reading culture, poor citations and referencing styles by students, untimely communication, and failure of some students to attend faculty field support. Further analysis revealed challenges of organising successful face-to-face workshops, inadequate counselling and guidance, inadequate action research supervision, students’ lack of ICT skills, inadequate library support, limited financial resource base, inadequate faculty support from the university management, and limited distance learners’ representation in their leadership and governance. The article concludes that building institutional capacity for distance education should be a driver to transform learner support challenges into opportunities for enhanced service delivery.
Keywords: university staff; learner support; in-service teachers; institutional challenges; distance education